A hydrothermally grown CdS nanograin-sensitized 1D Zr:α-Fe2O3/FTO photoanode for efficient solar-light-driven photoelectrochemical performance. Issue 7 (31st January 2017) - Mahadik, Mahadeo A.; Subramanian, Arunprabaharan; Ryu, Jungho; Cho, Min; Jang, Jum Suk
Abstract : A CdS nanograin sensitized 1D Zr:Fe2 O3 nanorod arrays nanostructure was hydrothermally synthesized and showed an excellent photoelectrochemical performance due to the combined effect of light absorption in CdS and effective charge transport in one dimensional Zr:Fe2 O3 nanorod arrays. Abstract : Well-defined CdS nanograin-sensitized one-dimensional (1D) Zr:α-Fe2 O3 nanostructured arrays with enhanced photoelectrochemical performance are synthesized directly on F-doped SnO2 (FTO) using the hydrothermal method. Owing predominantly to the appropriate photogenerated electron–hole separation and charge collection in 1D Zr:α-Fe2 O3 nanorods, hydrothermally deposited CdS/1D Zr:α-Fe2 O3 samples exhibit improved photocurrent density over CdS/Fe2 O3 nanosheets prepared by other methods. In our work, compared with 1D Zr:α-Fe2 O3, the CdS-sensitized 1D Zr:α-Fe2 O3 nanorod arrays show 1.9 times improved photoelectrochemical performance. Unfortunately, CdS nanograin-sensitized 1D Zr:α-Fe2 O3 nanorod arrays suffer from instability problem. Nickel hydroxide loading, however, can boost the photoelectrochemical performance of the heterojunction and also act as a protective layer that improves the stability of the Ni(OH)2 /CdS/1D Zr:α-Fe2 O3 electrode compared to CdS/1D Zr:α-Fe2 O3 . This enhanced PEC activity may be ascribed to the strong heterojunctions between CdS nanograins and 1D Zr:α-Fe2 O3 nanorod arrays as well as effective charge separation. This work will provide a new insight into the fabrication and protection of many new photosensitive electrode materials to engineer photoelectrochemical and photocatalytic devices in the near future.